2017
DOI: 10.1080/02688697.2017.1317717
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes after decompression and posterior fusion in patients with degenerative scoliosis

Abstract: Our findings suggest that decompression and posterior fusion in the patients with DS is an effective surgical method which is associated with satisfying clinical results in terms of improvement of postoperative LBP, radicular pain, and QOL, and correction of Cobb angle at 12 and 24 months after the surgery and restoration of sagittal alignment at 2 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…The surgical effectiveness of spinal surgery in leading to significant and sustained improvements in patient-reported disability and overall outcomes has been previously reported. 2,8,9,16,18 In our study, we observed the greatest magnitude of change in baseline to follow-up ODI; on the level of the individual SRS-22r domains, our cohort showed the greatest improvement from baseline in the self-image domain, with function, pain, and mental health showing less but still substantial and sig- nificant improvement from baseline. The finding that selfimage may be subject to the greatest benefit of all SRS-22r domains after correction of complex deformities has been previously reported.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The surgical effectiveness of spinal surgery in leading to significant and sustained improvements in patient-reported disability and overall outcomes has been previously reported. 2,8,9,16,18 In our study, we observed the greatest magnitude of change in baseline to follow-up ODI; on the level of the individual SRS-22r domains, our cohort showed the greatest improvement from baseline in the self-image domain, with function, pain, and mental health showing less but still substantial and sig- nificant improvement from baseline. The finding that selfimage may be subject to the greatest benefit of all SRS-22r domains after correction of complex deformities has been previously reported.…”
Section: Discussionsupporting
confidence: 44%
“…8 Other studies have reported substantial improvements in patient perceptions of disability as evidenced by significant reductions in ODI after spinal fusion. 10,12,15,18,21 Due to this potential for significant improvement in both perceptions of disability and self-image, longitudinal assessment of PROs in spinal deformity patients, especially in those undergoing complex fusions, is important in the evaluation of overall surgical outcomes. Collecting PROs at multiple follow-ups after spinal surgery is important, as patients continue to experience significant changes in healthcare quality-of-life measures owing to their deformity correction up to a year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients underwent partial decompressive laminectomy, PLF and spinal fixation with pedicular screws and rods (Implants International Ltd., Teesside industrial estate, Thornby, United Kingdom) [30,31]. PLF was done using bone graft and bone substitute.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In another study by Papp et al (9) the transoral vertebroplasty of C2 metastatic lesion was practiced, followed by posterior fusion. We believe that vertebroplasty not only alleviates pain but also enhances the biomechanical properties of the axis to withstand axial load and in the absence of pre-operative overt instability, posterior fusion is necessary (10). However, posterior fusion limits motion so it can negatively affect the quality of life.…”
mentioning
confidence: 99%